Exploration of graphitic carbon from crude oil vacuum residue - Ravi Dalsania; Hasmukh Gajera; Mahesh Savant (Carbon Trends)
Preparation of graphitic carbon from low value refinery waste has captivated immense interest in past years owing to its low cost and abundant nature. Successful utilization of petroleum vacuum residue is a major challenge in the petroleum industry. In this study pyrolysis of vacuum residue fractions has been carried out for the preparation of graphitic carbon like material. The vacuum residue fractions were obtained from three different crude oils originated from Middle East, Canada and South America. The purity of the Aromatic, Resin and Asphaltene (ARA) fractions were confirmed using TLC-FID which denoted complete separation. The chemical composition were determined using elemental analysis and it revealed ARA fractions to be carbon rich regardless of its origin. Further, sulphur content was found to be high in ARA fractions from Heavy Crude oil (HCO). The degree of polymerization and molecular weight measured using GPC specify that asphaltene has high accumulation with high molecular weight compared with aromatic and resins. ARA derived carbon and heat-treated materials were analysed by TGA, XRD and Raman spectroscopy to study microstructural changes in formation of graphite like material. Thermogravimetric analysis of all ARA samples revealed the different decomposition stages for pyrolyzed, calcined and graphitized samples. The results of XRD demonstrated that the distance between the planes (d-spacing) is above 3.35 Å for all high temperature treated ARA derived carbon materials irrespective of its origin, indicating formation of graphite like structure. In Raman analysis, the nature and intensity of G and D bands evolution during each step of pyrolysis is supporting XRD results for formation of highly ordered graphitic carbon material. Furthermore, understanding feed quality has direct influence on high efficiency, low costs and sustainability, the major issues for oil refinery business.